PEMANFAATAN MEDIA DIGITAL INSTAGRAM UNTUK MENGENALKAN BUDAYA TORAJA DALAM PEMBELAJARAN IPS - Anisa Salsabila; Krisnoviani; Hasni; Ahmadsyawaluddin (STKIP Subang, 2026)
This study analyzes the use of Instagram as a digital medium to introduce Torajan culture in social studies learning through a literature review method. This study used a qualitative approach with a literature review method that reviewed several relevant scientific articles. The results of the study indicate that Instagram, as a visual and interactive medium, is effective in presenting cultural content such as Tongkonan, Rambu Solo', Rambu Tuka', kinship systems, and mutual cooperation, thus helping students understand social studies concepts such as social interaction, values ​​and norms, and social stratification more concretely. In addition to improving cognitive understanding, Instagram use also fosters tolerance, appreciation for diversity, and pride in local culture. Thus, Instagram can be an innovative learning strategy that integrates digital technology, local culture, and character education to enhance students' understanding and appreciation of Torajan culture. This study aims to analyze the use of Instagram as a digital medium to introduce Torajan culture in social studies learning.